2016
DOI: 10.1177/0748233715589445
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive toxicity of chlorpyrifos tested in zebrafish (Danio rerio)

Abstract: This study was carried out to find out whether exposure to environmentally relevant concentration of chlorpyrifos (CP) modulates reproductive competence. To understand this, eight adult male and eight adult female zebrafish (Danio rerio) were exposed to 200 µg/L of CP for 24, 48, 72, and 96 h. Vitellogenin levels did not show much change in female fish, whereas in male the levels increased with increasing exposure time thereby indicating estrogenecity of the toxicant. Attenuation of serum 11-ketotestosterone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…The histopathological alterations observed in our study were dose-and duration-dependent because after 15 and 45 days of exposure to 150 µg/L, cytoplasmic degenerations like CC and CR were observed, indicating the negative feedback of estrogens to hypothalamic-pituitary-gonadal axis of this fish (Tillitt et al, 2010). Earlier studies demonstrated a strong negative correlation between the damaged ovarian structures and levels of estrogen production in fish exposed to different pesticides (Maxwell and Dutta, 2005;Manjunatha and Philip, 2016). Deka and Mahanta (2012) observed cytoplasmic degenerations in Stinging Catfish (Heteropneustes fossilis) ovary when exposed to 200 µg/L malathion for 10 days.…”
Section: Effects Of Chlorpyrifos On Ovarymentioning
confidence: 85%
See 4 more Smart Citations
“…The histopathological alterations observed in our study were dose-and duration-dependent because after 15 and 45 days of exposure to 150 µg/L, cytoplasmic degenerations like CC and CR were observed, indicating the negative feedback of estrogens to hypothalamic-pituitary-gonadal axis of this fish (Tillitt et al, 2010). Earlier studies demonstrated a strong negative correlation between the damaged ovarian structures and levels of estrogen production in fish exposed to different pesticides (Maxwell and Dutta, 2005;Manjunatha and Philip, 2016). Deka and Mahanta (2012) observed cytoplasmic degenerations in Stinging Catfish (Heteropneustes fossilis) ovary when exposed to 200 µg/L malathion for 10 days.…”
Section: Effects Of Chlorpyrifos On Ovarymentioning
confidence: 85%
“…The aquatic contamination by pesticides used in agriculture may constitute potential (eco)toxicological risks to non-target aquatic organisms of different trophic levels in a food chain i.e. primary producers (Daam et al, 2008a;Malev et al, 2012;Liu et al, 2013;Kumar et al, 2014), invertebrates (Maltby et al, 2005;Palma et al, 2009;Rubach et al, 2011;Roessink et al, 2013;Van den Brink et al, 2016), and fish (Tillitt et al, 2010;Marimuthu et al, 2013;Manjunatha and Philip, 2016;, when exceeding the threshold levels.…”
Section: Potential Effects Of Pesticides On the Aquatic Environmentmentioning
confidence: 99%
See 3 more Smart Citations